Prevalence of Fibromyalgia in Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2014)
This study sought to determine the prevalence of fibromyalgia syndrome and to identify whether fibromyalgia was associated with various clinical symptoms and laboratory parameters in hemodialysis patients. One hundred and forty-eight hemodialysis patients were examined for fibromyalgia symptoms according to the American College of Rheumatology criteria. Demographic characteristics, as well as causes of kidney failure, dialysis duration, and symptoms related to fibromyalgia were investigated. Of 148 patients, 18 (12.2%) were diagnosed with fibromyalgia. Patients with fibromyalgia had significantly poorer sleeping satisfaction than the control group (P = .02). The Beck Depression Inventory score was higher in 77.8% of the fibromyalgia patients than that in the control group (P = .006), but there was no significant difference in the anxiety score between the two groups (P = .86). In conclusion, there was a higher prevalence of fibromyalgia in hemodialysis patients than previously reported. Sleep disturbances and depression levels correlated with fibromyalgia.